Bleomycin-enhanced alternative splicing of fibroblast growth factor receptor 2 induces epithelial to mesenchymal transition in lung fibrosis. Issue 6 (14th November 2018) - Chen, Kui-Jun; Li, Qing; Weng, Chang-Mei; Duan, Zhao-Xia; Zhang, Dong-Dong; Chen, Zhi-Qiang; Chen, Jing; Wang, Jian-Min
Abstract : Idiopathic pulmonary fibrosis (IPF) is an important public health problem, and it has few treatment options given its poorly understood etiology; however, epithelial to mesenchymal transition (EMT) of pneumocytes has been implicated as a factor. Herein, we aimed to explore the underlying mechanisms of lung fibrosis mediated by EMT, with a focus on the alternative splicing of fibroblast growth factor receptor 2 (FGFR2), using bleomycin (BLM)-induced lung fibrotic and transgenic mouse models. We employed BLM-induced and surfactant protein C (SPC)-Cre and LacZ double transgenic mouse models. The results showed that EMT occurred during lung fibrosis. BLM inhibited the expression of epithelial splicing regulatory protein 1 (ESRP1), resulting in enhanced alternative splicing of FGFR2 to the mesenchymal isoform IIIc. BLM-induced lung fibrosis was also associated with the activation of TGF-β/Smad signaling. These findings have implications for rationally targetted strategies to therapeutically address IPF.